Impacts of water and saline stress on Erythrina velutina Wild seedlings - Aderaldo, Francisco Ícaro Carvalho; Ferreira, Gabriela de Sousa; Sousa, Janacinta Nogueira de; Brito, Paulo Ovídio Batista de; Gondim, Franklin Aragão (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2022)
This article analyzed the growth of mulungu (Erythrina velutina Wild) seedlings, subjected to saline stress and associated with irrigation suspension. This experiment was carried out in 5-liter pots, irrigated at 50% of field capacity. The experimental design was completely randomized, consisting of six treatments: T1- Irrigation with distilled water (Testimony); T2 - Irrigation with 50 mM NaCl solution; T3 – Irrigation with 100 mM NaCl solution; T4 - Irrigation with distilled water with irrigation suspended at 15 days after sowing (DAS); T5 - Irrigation with 50 mM NaCl solution with suspended irrigation at 15 DAS; T6 - Irrigation with 100 mM NaCl solution with suspended irrigation at 15 DAS. The control treatment had a smaller amount of deleterious effects for the seedlings, being, therefore, the most suitable for the cultivation of mulungu. Salinity caused reductions in the analyzed growth variables, such as total fresh matter, root and shoot, total dry matter, root and shoot, height, stem diameter and number of leaves. These effects were intensified in plants submitted to 100 mM of NaCl and irrigation suspension.